BID: BioWorld Interactive Dictionary - Okpoluaefe Godspower Udezi, Suruthimitra Okpoluaefe; Subramaniam, Dineshwaran Naidu; Parameswaran, Kavesha; Tharik, Jakir Hussain; Saad, Wan Zuhainis (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
Education today is considered a mere act of going an institution and start memorising facts. A report from Ofsted suggested boring lessons could be blame for high truancy rates at some schools (Paton, 2009). It is believed that this is the perception of teenagers as they have difficulty seeing the links between ‘distinct’ chapters. BioWorld Interactive Dictionary (BID) ensures that learning is not boring as it is interactive in nature, with the incorporation of augmented reality and games. It boosts students’ interests and encourages them to learn using text books and our unconventional dictionary hand-in-hand.